PRODIACOR: A patient-centered treatment program for type 2 diabetes and associated cardiovascular risk factors in the city of Corrientes, Argentina. Study design and baseline data - Gagliardino, Juan Jose (2007)
Objective: To implement a controlled clinical trial (PRODIACOR) in a primary care setting designed 1) to improve type 2 diabetes care and 2) to collect cost data in order to be able to measure cost-effectiveness of three system interventions (checkbook of indicated procedures, patient/provider feedback and complete coverage of medications and supplies) and physician and/or patient education to improve psychological, clinical, metabolic and therapeutic indicators. All three Argentinean health subsectors (public health, social security and the private, prepaid system) are participants in the study. Patients of participating physicians were randomly selected and assigned to one of four groups: control, provider education, patient education, and provider/patient education; the system interventions were provided to all four groups. Baseline results: Mean BMI was 29.8 kg/m2; most subjects had blood pressure, fasting glucose and total cholesterol above targets recommended by international standards. Only 1% had had microalbuminuria measured, 57% performed glucose self-monitoring, 37% had had an eye examination and 31% a foot examination in the preceding year. Ten percent, 26% and 73% of people with hyperglycemia, hypertension and dyslipidemia, respectively, were not on medications. Most patients treated with either insulin or oral antidiabetic agents were on monotherapy as were those treated for hypertension and dyslipidemia. WHO-5 questionnaire scores indicated that 13% of the subjects needed psychological intervention.  Conclusions: Baseline data show multiple deficiencies in the process and outcomes of care that could be targeted and improved by PRODIACOR intervention.